Munnur hestsins við frumtamningu : forathugun á íslenskum tamningatrippum - Mai, Christina, 1986- (2012)
A pilot study was designed to assess morphological changes of the oral cavity of Icelandic youngsters during their first training phase, and to describe other reactions expressed by the horses when introduced to the headgear equipment. For ten weeks, eight horses were started with commonly used headgear equipment in Iceland, applying methods of first basic training practiced at Hólar University College. Three oral examinations were performed on the horses at the beginning, middle and end of the training period to assess the oral mucosa and the process of tooth shedding. Severe congenital abnormalities were observed in the tooth shedding in one horse that was consequently excluded from the study. Otherwise, the tooth shedding appeared to be in accordance with descriptions from other breeds in the literature. Thickening of the buccal mucosa was confirmed in three horses before training started, one with a mild lesion in this location. At the middle of the training period, comparable thickening was found in all horses except one, most likely as a reaction to pressure from the rope halter used during this period of training. At the end of the study, the buccal mucosa had in most cases normalized, while pressure reactions were now observed at the inside of the corners of the mouth in all horses, developing to a mild lesion in one case. These findings suggest that head gear equipment affects oral mucosa at predetermined locations, reflecting pressure points applied by the respective equipment. This happened without underlying abnormalities of the teeth. Care must be taken to avoid further development of these reactions to pressure lesions. Further reseach is needed to confirm these results and provide evidence-based preventive measures to maintain good oral health in the ridden horse. Verkefni tetta er forathugun á teim breytingum sem verda í munnholi hesta á medan á hefdbundinni frumtamningu stendur og lysir auk tess fyrstu vidbrögdum hesta vid beislisbúnadi. Átta trippi á fjórda vetri voru frumtamin í 10 vikur med ...